Investigation of Some Physiological and Biochemical Parameters in Pseudomonas syringae-Infected Tomato Plants - BERBER, I.; ONLU, H.; EKIN, S.; BATTAL, P.; E. EREZ, M. (Asian Journal of Chemistry, 2010)
In the present study, the levels of manganese, magnesium, plant hormones (indole-3-acetic acid and abscisic acid), sugars (fructose and maltose), total chlorophyll and carotenoid contents in tomato plants following inoculation with Pseudomonas syringae pv. tomato were investigated. The trace element analysis showed that the levels of Mn significantly decreased in bacterium-infected tomato plants, comparing to the healthy plants. In contrary, the content of Mg in the bacteriuminfected plants was higher than the uninfected plants. Manganese deficient in the bacterium-infected plants might be an important indicator against attempted bacterial infection. The results of phytohormone analysis showed that there may be an opposite relationship between the concentrations of endogenous indole-3-acetic acid and abscisic acid and the enhance disease resistance in bacterium-infected tomato plants. Therefore, it seems that indole-3-acetic acid, like abscisic acid, acts as a negative regulator of plant defense. Fructose concentrations increased in second, fourth, eight days after treatment with pathogen, but there was a decrease in tenth days. However, maltose levels decreased in all the periods after inoculation with the pathogen bacterium comparing to the control healthy plants. These results were also affirmed to the reduction in the total contents of chlorophyll and an increase of total carotenoids in the bacterium infected-plants. The investigation confirmed that there are complex relationships among trace element levels, endogenous plant hormone and sugar in the regulation of defense mechanisms against attacks by bacterial pathogens.